Prevalence and clusters of modifiable cardiovascular disease risk factors among intra-city commercial motor vehicle drivers in a Nigerian metropolitan city (2020)
Background: Commercial motor vehicle drivers (CMVDs) have worst health profiles among different occupations, yet the presence of clusters of cardiovascular disease (CVD) risk factors in this group have not been described in a resource-limited setting. Objectives: The prevalence of CVD risk factors and the clusters among CMVDs was evaluated. Design: A cross-sectional descriptive study. Setting: Four motor parks in three local government areas of Ibadan city, Nigeria. Participants: Consented and conveniently sampled 152 intra-city CMVDs aged ≥ 18 years. Main outcome measures: Prevalence of CVD risk factors (hypertension, diabetes, high triglyceride, low HDLc, high waist-hip ratio, central obesity, physical inactivity, smoking, alcohol, and overweight/obesity) and their clusters were determined. Results: All participants were male from 20 – 77 years old. Most of the CMVDs were physically inactive (80, 52.6%), take alcohol (78, 51.3%), and few smokes (35, 12.4%). The prevalence of hypertension, diabetes, hypertriglyceridemia, obesity, and central obesity were 36.2%, 5.9%, 23.7%, 4.6%, and 5.3%, respectively. Four clusters of CVD risk factors in the CMVDs with the prevalence of 36.2%. 33.5%, 17.1% and 13.2% were identified with significant differences (p<0.05) in the risk factors. Conclusion: The prevalence of diabetes, obesity, central obesity, and smoking was low while the prevalence of hypertension and hypertriglyceridemia was moderate among the CMVDs, but the prevalence of alcohol intake and physical inactivity were high. Four distinct clusters of CVD risk factors were observed among the drivers.